Pengaruh Perbandingan Terigu dan Pati Garut (Maranta arundinacea L.) Termodifikasi Autoclaving-Cooling Terhadap Karakteristik Mi Basah - Gandhes Sekarjati, Agnes Monika; Diah Puspawati, Gusti Ayu Kadek; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 1 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i01.p02, 2023)
This study aimed to determine the ratio effect of wheat flour and autoclaving-cooling modified arrowroot starch on the characteristics of wet noodle and to obtain the correct comparison of wheat flour and autoclaving-cooling modified arrowroot starch to produce wet noodle with the best characteristics. The research method used a Randomized Block Design with comparison treatment of wheat flour and autoclaving-cooling modified arrowroot starch consisted in 6 levels (100:0, 90:10, 80:20, 70:30, 60:40, 50:50). The treatment was repeated 2 times to obtain 12 experimental units. The data were analyzed statistically using the variance test and if the treatment had a significant effect to observed variables, it was continued with Duncan’s Multiple Range Test. The result showed that the comparison of wheat flour and autoclaving-cooling modified arrowroot starch has a significant effect (P<0.05) on moisture content, ash content, protein content, elasticity, water absorption, and cooking loss. The best treatment was the 70:30 comparison of wheat flour and autoclaving-cooling modified arrowroot starch with the characteristics 34.59% of moisture content, 0.33% of ash content, 6.12% of protein content, 13,00% of elasticity, 425,26% of water absorption, 11,47% of elasticity, also sensory evaluation color was liked, aroma was liked, texture was chewy and liked, taste was liked, and overall acceptance was liked.